1992
DOI: 10.1111/j.1476-5381.1992.tb13415.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a 5‐lipoxygenase inhibitor and leukotriene antagonist (PF 5901) on PAF‐induced airway responses in neonatally immunized rabbits

Abstract: 1 Aerosol administration of platelet activating factor (PAF) (80pjgml' for 60min) to neonatally immunized rabbits caused bronchoconstriction which was far in excess of that produced by a comparable aerosol of bovine serum albumin (BSA) D4 antagonist, at a dose of 10 mg (direct intratracheal administration) significantly inhibited the airway resistance (RL) component of the bronchoconstriction induced by PAF in neonatallyimmunized rabbits. Doses of 10 mg, 3 mg and 1 mg PF 5901 (direct intratracheal administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 82 publications
2
15
0
Order By: Relevance
“…In agreement with previous studies PAF was found to induce an influx of inflammatory cells into the airways (predominantly neutrophils and eosinophils) as assessed by bronchoalveolar lavage (BAL) (Herd et al, 1992). The accumulation and activation of inflammatory cells within the airways has been suggested to lead to epithelial damage causing the exposure of nerve endings in the bronchial lumen, which are thought to initiate an increase in airway responsiveness (Barnes, 1986).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In agreement with previous studies PAF was found to induce an influx of inflammatory cells into the airways (predominantly neutrophils and eosinophils) as assessed by bronchoalveolar lavage (BAL) (Herd et al, 1992). The accumulation and activation of inflammatory cells within the airways has been suggested to lead to epithelial damage causing the exposure of nerve endings in the bronchial lumen, which are thought to initiate an increase in airway responsiveness (Barnes, 1986).…”
Section: Discussionsupporting
confidence: 88%
“…This observation supports previous findings in this model suggesting that eosinophil infiltration and airway hyperresponsiveness may be unrelated events. The 5-lipoxygenase activating protein (FLAP) inhibitor, PF 5901, did not inhibit PAF-induced cell infiltration despite inhibiting the associated airway hyperresponsiveness (Herd et al, 1992) and pretreatment of rabbits with capsaicin has been shown to inhibit airway hyperresponsiveness but not the pulmonary eosinophil infiltration induced by PAF (Spina et al, 1991). Furthermore, in guinea-pigs, capsaicin will inhibit allergeninduced airway hyperresponsiveness without modifying pulmonary eosinophil influx (Ladenius & Biggs, 1989;Matsuse et al, 1991) and certain cytokines have been shown to cause pulmonary eosinophilia without eliciting airway hyperresponsiveness (Kings et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PAF has been employed in this study to induce airway hyperresponsiveness in rabbits as we have previously reported that this is a useful test system for the evaluation of pharmacological agents and is simpler and more robust method than antigen challenge. We have utilized antigen-immunized rabbits in this study as we have previously shown that PAF can induce airway hyperresponsiveness to inhaled histamine in all neonatally immunized rabbits to some degree (Herd et al, 1992), whereas only in some, but not all normal rabbits (Coyle et al, 1990;Herd et al, 1992). Therefore, in the present study we have investigated the effects of heparin and related compounds on PAF-induced airway hyperresponsiveness and pulmonary cell infiltration in neonatally antigen-immunized rabbits in vivo.…”
Section: Introductionmentioning
confidence: 99%